Food additives: the impact they can cause on human health (Research, Society and Development, 2022)
This study aims to contextualize, through a systematic literature review, the risks that can be caused by the consumption of food additives. Food additive is any ingredient used during any stage of the production of a food, without the purpose of nourishing, but rather of modifying its physical, chemical, biological and sensory characteristics. The industrialization of food has revolutionized food, influenced by the great population growth and the great urbanization, presenting advantages in relation to durability, practicality and price, but also, being able to cause disadvantages when related to health. The objective of this work is to show some effects that food additives cause on human health, given that the current food model has become largely industrialized and massified. This is a literature review study with a qualitative approach carried out in 2022, having as a database: SCIELO, LILACS, MEDLINE/PUBMED, where they went through exclusion and inclusion criteria, resulting in 10 studies included in this review. The results demonstrate that the consumption of processed or industrialized foods has negative effects on health, children appear as a vulnerable group, due to the potential consumption of foods with food additives, particularly artificial dyes. The results indicate that studies on the consumption of food additives should serve as a basis for the development of food and nutrition surveillance strategies, in order to promote healthy eating habits.